Defensa comunitaria y culturas del terror: Crimen organizado y violencia de Estado en comunidades originarias de Guerrero, México. - Delgado, Inés Giménez (Journal of Latin American & Caribbean Anthropology, 2022)
Rich in raw materials, the state of Guerrero, Mexico, is one of the main enclaves of opium production, mineral extraction, and a focus for the multiplication of armed actors in Latin America, which, together with the overlapping of counterinsurgent violence in the past, post‐colonial violence and the militarization of the policies of the so‐called fight against drugs has contributed to very high rates of multiple and continuous violence. Drawing on investigative ethnographic fieldwork, testimonial work and a hemerographic review in Guerrero, this article investigates how the entanglement between state, para‐state, criminal and community actors leads to some short of "state of exception," as well as to the emergence of forms of territorial organization. Through a case study in rural Nahua communities of Chilapa and echoing studies on the anthropology of violence, state anthropology and anarchist anthropology, we discuss the culture of terror at the margins of the state and the strategies of community and everyday resistance, that, although seek to ensure their political and economic survival, are at risk of being captured by some forms of the violence they fight.